Effects of pH and Storage Time on the Stability of Papaya and Carrot Extracts - Juliana, Juliana; Indrawati, Renny; Yuliati, Leny (Ma Chung Research Center for Photosynthetic Pigments, 2019)
Papaya and carrot are rich in natural pigments, especially b-carotene. Unfortunately, in most cases, natural pigments are less stable than the synthetic ones when they are put in a variety of treatment conditions, such as pH. In this work, the stability of the papaya and carrot extracts were evaluated in various pH, which ranges of 1-10 for 7 days. The extracts were obtained by a slow juicer, followed by encapsulation and drying by a freeze dryer. The extracts were then dispersed in buffer solutions and the chroma and color difference (DE) values were calculated from the obtained lightness (L*), redness (a*), and yellowness (b*). The results showed that carrot extract was better than the papaya extract in terms of chroma values. It was also shown that both extracts were not stable under acidic condition, but more stable in neutral to alkaline condition. The acid condition facilitated the cleavage of the conjugated bonds in the b-carotene, which in turn caused the color degradation in the papaya and carrot extracts.